Analysis of transient combustion with the use of contemporary CFD techniques. (15th November 2019) - Bykov, V.; Kiverin, A.; Koksharov, A.; Yakovenko, I.
Highlights: Dissipation-free method CABARET is adopted for unsteady combustion modeling. Novel pseudo-spectral method is described and applied for unsteady combustion modeling. Set of verification and validation tests is proposed to assess methods capabilities. Developed assessment procedure is general and applicable for any CFD technique. Abstract: The paper introduces the results of the validation of two contemporary CFD techniques for numerical analysis of transient combustion phenomena. Dissipation-free numerical technique (CABARET) and pseudo spectral method are outlined and validated by using several benchmarks. Three basic test routines are suggested among which are: one-dimensional steady flame, one-dimensional and two-dimensional unsteady flames. It is shown that both analyzed numerical techniques possess a set of advantages including extremely low values of scheme dissipation and dispersion. This allows reproducing the evolution of non-steady multidimensional flows with high accuracy. The disadvantages of conventional finite-difference schemes and the limits of their applicability are discussed. A full description of the proposed test routines is provided; one can utilize them to carry out validation of the reactive CFD codes.